Social and economic conditions of fishermen catching lobsters in the Pangandaran Coastal Area, West Java Province - Rahayu, Indriyani; Herawati, Titin; Nurhayati, Atikah; MS, Yuniarti; HS, Asep Agus; Sunarto, Sunarto (Universitas Malikussaleh, 2023)
This study aims to determine the socio-economic conditions of lobster fishermen at 3 stations, namely Station 1 Madasari Beach, station 2 Pantai Timur Pangandaran, station 3 Pamotan Village, Majingklak District, Pangandaran Regency, West Java Province. Data collection was carried out from October 2022 - February 2023 through field surveys. This research used a descriptive method which used 90 respondents, 30 respondents at each station. Collecting data using interview techniques, observation, questionnaires, and documentation. The results of the study show that in general the age of fishermen is between 43-52 years with a junior high school level of education who have a work experience level of 11-20 years, and more than 51% of lobster fishermen in Pangandaran waters have family dependents where in one family the number of dependents is more than 3 people. Respondents income at 3 stations in Pangandaran Regency ranges from 100,000 to 200,000 per day, and the total expenditure in one month is Rp. 2,000,000 to IDR 2,500,000. In general, the fishermen's houses at the 3 stations are good and livable, and some of the fishermen's children have continued their studies at a higher level, namely college. Lobster fishermen do most of their main work as fishermen, and very few have other jobs besides working as fishermen.Keywords: Lobster Fishermen; Pangandaran; Social and Economic